Internet of Things (IoT) based air quality index measurement system for Dhaka city - Aurangajeb, Raoha; Karmaker, Sajib; Kamal, Md. Ridhwan; Tasdid, M. Sadman (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.